RANCANG BANGUN SISTEM PEMANEN ENERGI EXHAUST FAN DENGAN DIFFUSER TURBIN ANGIN SUMBU HORIZONTAL - Vasabri Genta Maulana, Edyama; Sukerayasa, I Wayan; Indra Partha, Cok Gede (Jurnal SPEKTRUM; Vol 8 No 2 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i02.p21, 2021)
Utilization of waste energy from exhaust fan air needs to be optimized considering there is great potential where exhaust fan is widely used in the industrial sector. Exhaust wind from exhaust fan can be utilized to generate electricity with horizontal wind turbine. The characteristics of exhaust energy from exhaust fan that spreads and has medium to low speed, therefore its requires an optimization to get maximum wind energy from exhaust fan, one of them by the addition of a diffuser that can increase the performance of wind turbines by focusing the wind around the rotor. Designing diffuser conducted using AutoDesk Inventor and simulation CFD (Computational Fluid Dynamic) with SolidWorks. The results of this study indicate, horizontal wind turbine with diffuser can increase wind turbine power up to 47.61% and increase turbine rotational speed (rpm) up to 23.48% compared to wind turbines without a diffuser.